Selecting an optimal model of cooperation in the vegetable industry in Russia: vertical integration, agrarian dies, clusters. (May 2019) - Mindlin, Yu; Lebedev, N
Abstract: The article gives a brief description of the existing problems of vegetable growing in the Russian Federation. It is shown that hierarchical (in the form of vertical integration) or network (in the form of agrarian fillers or clusters) models of the functioning of the vegetable industry can be used to solve them. A comparative analysis of these models is provided in the paper. It is shown that a rapid increase in production can be achieved on the basis of vertical integration. However, for ensuring the sustainable development of the industry, it is necessary to use network models. Thus, stable and efficient functioning of the vegetable industry in our country should be based on the balance of hierarchical and network models.